The Influence of Gender on Students’ Academic Achievement in a Nursing Diploma Program - Herlina, Nunung; Solichin, Solichin; Dirdjo, Maridi M.; Ramli, Akhmad (Universitas Muhammadiyah Kalimantan Timur, 2024)
Different from education in general, nursing education is dominated by the female gender both in Indonesia and in the world. There is still debate about whether gender has an influence on student achievement, including in nursing education. Research objective is to find out the influence of gender on the achievement of nursing diploma level students who are dominated by female gender. This research is a quantitative research, namely retrospective descriptive. The population in this study were students of the Nursing Diploma Three Study Program with a sample size of 93 students. The sampling technique used in the research was total sampling. The instrument used in this research is secondary data, namely by looking at the documentation of student gender biodata, and learning achievement is the Cumulative Achievement Index (GPA) from the student’s Study Result Card after graduation. The statistical test used in analyzing this research is the independent t test; with a significance level of 0.05. Based on bivariate analysis, it is known that there is a relationship between gender and learning achievement with a significance value of 0.03 <0.05. The results indicate that there is a difference in the achievement of female students compared to male students. Female students have an average Grade Point Average of 3.51 with honors, while male students have an average Grade Point Average of 3.44 with a satisfactory grade. From the research it is concluded that there is an influence of gender on the achievement of nursing diploma program students.